Preparation of graphene - based photocatalyst for environmental application - Chong, Ying Yan (2015)
Semiconductor-mediated photocatalysis has been widely explored in the treatment of water and wastewater containing EOC, due to its ability to completely mineralize organic pollutants and transforming them into non-toxic inorganic compounds such as carbon dioxide and water. However, problems associated with the existing photocatalysts such as Titanium Dioxide (TiO2) include the fast rate of electron-hole pair recombination, and the need for UV light irradiation that consumes more energy. Copper sulfide (CuS) emerged to be a potential semiconductor as it turns into a superconductor at low temperatures and can be photo-excited under visible light spectrum, hence lowering the operational costs. However, there are limitations to the application of CuS such as its reduced surface area caused by nameplates aggregation, resulting in low photocatalytic activity. Hence, the photocatalyst has to be modified to further increase its photocatalytic activity. In this study, a hybrid nanocomposite Graphene-based photocatalyst (GO-COOH-CuS-Ag) was synthesised via a facile two-phase (toluene-water) method, with the incorporation of carboxylic acid functionalised graphene oxide sheets (GO-COOH), silver (Ag) nanoparticles, and copper sulfide (CuS) nanoplates that were synthesised individually. GO-COOH was obtained through the modified Hummers’ method with the addition of chloroacetic acid to achieve the carboxylic acid functionalised groups. Pure CuS nanoplates and oleylamine-capped Ag nanparticles were synthesized by a simple hydrothermal method, using copper ethyl xanthate and silver nitrate respectively. The precursors’ CuS contents were varied to obtain a sample with preferential morphology. The report revealed that the hybridisation of GO-COOH sheets, CuS nanoplates and Ag nanoparticles provides a synergistic effect that combines the advantageous properties of all three constituents, resulting in better photodegradation activity towards dye (Rhodamine B (RhB)) and photo-disinfection antibacterial efficiency, under solar irradiation. The hybridisation led to: (i) red shift of light absorption associating to lower energy consumption, (ii) larger surface area for the adsorption of contaminants including dye and bacteria, (iii) efficient electron-hole separation and low recombination rate of the charge carriers. Overall, the hybrid nanocomposite GO-COOH-CuS-Ag appears to have effectively surmount the significant shortcomings of existing photocatalysts. Thus, this work presents the feasibility of fabrication and provides a promising solution for potential water treatment applications.